Rare earth elements induce cytoskeleton-dependent and PI4P-associated rearrangement of SYT1/SYT5 endoplasmic reticulum–plasma membrane contact site complexes in Arabidopsis. (17th March 2020) - Lee, EunKyoung; Santana, Brenda Vila Nova; Samuels, Elizabeth; Benitez-Fuente, Francisco; Corsi, Erica; Botella, Miguel A; Perez-Sancho, Jessica; Vanneste, Steffen; Friml, Jiří; Macho, Alberto; Azevedo, Aristea Alves; Rosado, Abel
Abstract : Rare earth elements induce ER membrane remodeling and increase ER–PM connectivity in a process that involves phosphoinositide-associated reorganization of synaptotagmin-tethering complexes. Abstract: In plant cells, environmental stressors promote changes in connectivity between the cortical endoplasmic reticulum (ER) and the plasma membrane (PM). Although this process is tightly regulated in space and time, the molecular signals and structural components mediating these changes in interorganelle communication are only starting to be characterized. In this report, we confirm the presence of a putative tethering complex containing the synaptotagmins 1 and 5 (SYT1 and SYT5) and the Ca 2+ - and lipid-binding protein 1 (CLB1/SYT7). This complex is enriched at ER–PM contact sites (EPCSs), has slow responses to changes in extracellular Ca 2+, and displays severe cytoskeleton-dependent rearrangements in response to the trivalent lanthanum (La 3+ ) and gadolinium (Gd 3+ ) rare earth elements (REEs). Although REEs are generally used as non-selective cation channel blockers at the PM, here we show that the slow internalization of REEs into the cytosol underlies the activation of the Ca 2+ /calmodulin intracellular signaling, the accumulation of phosphatidylinositol-4-phosphate (PI4P) at the PM, and the cytoskeleton-dependent rearrangement of the SYT1/SYT5 EPCS complexes. We propose that the observed EPCS rearrangements act as a slow adaptive response to sustained stress conditions, and that this process involves the accumulation of stress-specific phosphoinositide species at the PM.